ANALISIS FAKTOR RENDAHNYA KEMAMPUAN MEMBACA DAN MENULIS SISWA KELAS II SD NEGERI 2 MRANTI - Safira Roesi; Rintis Rizkia Pangestika; Suyoto (LPPM STKIP Bina Bangsa Meulaboh, 2024)
This research discusses factors in the low reading and writing abilities of class II students at SD Negeri 2 Mranti. This research aims to determine the factors of low reading ability and writing ability in class II students at SD Negeri 2 Mranti. This research uses a descriptive qualitative approach by explaining and presenting the results of the research that has been carried out. This research describes the factors behind the low reading and writing ability of class II students at SD Negeri 2 Mranti. The data collection techniques used in this research are observation, interviews, tests, questionnaires and documentation. The research results show that the factors behind students' low reading ability and writing ability are internal factors and external factors. Internal factors for low reading ability are interest, talent and health. External factors for low reading ability are family environmental factors and school environmental factors. Meanwhile, the internal factors of low writing ability are physical factors, physical health and spiritual factors include motivation, interest, talent of students. External factors for low writing ability are family factors and school factors.